2009
DOI: 10.1186/1471-2180-9-255
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of Aspergillus niger: Lactate added in starch-containing medium can increase production of the mycotoxin fumonisin B2 by modifying acetyl-CoA metabolism

Abstract: Background: Aspergillus niger is a filamentous fungus found in the environment, on foods and feeds and is used as host for production of organic acids, enzymes and proteins. The mycotoxin fumonisin B 2 was recently found to be produced by A. niger and hence very little is known about production and regulation of this metabolite. Proteome analysis was used with the purpose to reveal how fumonisin B 2 production by A. niger is influenced by starch and lactate in the medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 71 publications
1
26
1
Order By: Relevance
“…To compensate for this, a larger fraction of mitochondrial AcCoA must originate from pyruvate, which requires a higher flux through glycolysis. This argument is supported by the reported correlation between the glycolytic flux and the pool size of acetyl-CoA [34]. Sorensen et al (2009) observed that addition of lactate, led to an increased pool of AcCoA, which caused an up-regulation of the rate-limiting enzyme of the pentose phosphate pathway (PP pathway), Glucose-6-phosphate dehydrogenase [34].…”
Section: Discussionmentioning
confidence: 92%
“…To compensate for this, a larger fraction of mitochondrial AcCoA must originate from pyruvate, which requires a higher flux through glycolysis. This argument is supported by the reported correlation between the glycolytic flux and the pool size of acetyl-CoA [34]. Sorensen et al (2009) observed that addition of lactate, led to an increased pool of AcCoA, which caused an up-regulation of the rate-limiting enzyme of the pentose phosphate pathway (PP pathway), Glucose-6-phosphate dehydrogenase [34].…”
Section: Discussionmentioning
confidence: 92%
“…For example fumonisins B 2 , B 4 and B 6 are produced by Aspergillus niger (Frisvad et al, 2007;Sørensen et al, 2009;Mogensen et al, 2009Mogensen et al, , 2010Månsson et al, 2010), while fumonisins B 1 , B 2 and B 3 are produced by a series of Fusarium species from four sections: Arthrosporiella, Dlaminia, Elegans and Liseola (Fotso et al, 2002;Rheeder et al, 2002;Sewram et al, 2005). It is not yet known whether the production of similar mycotoxins in widely different genera is caused by horizontal gene transfer (for example mobile chromosomes) or by parallel evolution.…”
Section: Mycotoxigenic Fungimentioning
confidence: 99%
“…They reduce the disulfide bonds and enhance the protein solubility. Even ampholytes at a concentration of 0.5% to 0.8% are used for increased protein solubility, however it must be taken into consideration for the focusing procedure [26]. Proteases inhibitor cocktails or PMSF are added to the homogenization buffer to deactivate the strong fungal proteases and lysis of the proteins [10].…”
Section: Sample Homogenisationmentioning
confidence: 99%